Implementation of SWOT in Improving the Image of Islamic Boarding Schools at the Islamic Boarding School - Supriyyadi, Supriyyadi; Nadir, Mirhabun; Ikhwan, M. Bisri (Instructional Development Journal, 2025)
Abstract: Darussalam Islamic Boarding School Blokagung Banyuwangi, as a traditional Islamic educational institution, faces the challenge of competitiveness in the modern era. SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis is a relevant tool in viewing the position of Islamic boarding schools in this context. This study aims to investigate the potential and obstacles of Islamic boarding schools in increasing their competitiveness. This research uses a qualitative approach with data collection techniques through interviews and observation. Data analysis in this research uses the Milles and Huberman analysis model including data reduction, data presentation and drawing conclusions. The results show that the SWOT analysis at the Darussalam Ponpes Blokagung Banyuwangi was carried out by exploring information related to the analysis of needs, opportunities, challenges and weaknesses in the Ponpes. Information was gathered through stakeholders in the Pope, such as kyai as Islamic boarding school leaders, managers (caretakers and teachers, dormitory supervisors, asatidz councils, students and related parties such as administration, student guardians, etc. The potential power to support campus development is the heritage element culture, religious education, infrastructure, social networks. The weaknesses include: limited resources, modern skills.